Adaptation finance gap - Savvidou, Georgia; Canales, Nella; Haque, Nabil; Pauw, Pieter; Mbeva, Kennedy; Zamarioli, Luis (United Nations Environment Programme, 2023)
Key messages ▶ For the five years following the Paris Agreement’s entry into force (2017–2021), finance for adaptation from international public sources to developing countries remained at or below US$25 billion per year, or approximately US$3 per person per year. In 2021, there was a 15 per cent decrease from 2020 levels, down to US$21 billion. ▶ In the same five-year period, the disbursement ratio for adaptation finance (at 66 per cent) was lower than for development finance overall (at 98 per cent): this indicates specific barriers to adaptation that hinder the implementation of projects in developing countries. ● These barriers include low grant-to-loan ratios, failure to consider local issues when planning and designing projects, limited technical capacity among decision makers, and misalignment between the duration of the approval and disbursement process and the shorter-term mandates of national and local governments. ▶ In the 2017–2021 period, less than 17 per cent of commitments were dedicated to projects with a specific focus on local communities. While this is an increase from previous levels, these low levels exist despite increasing understanding of the importance of local communities’ agency and involvement in adaptation projects. ▶ In the same period, the share of grants as a proportion of the total finance for adaptation for least developed countries (LDCs) (at 52 per cent) was substantially higher than that of non-LDCs (26 per cent). Small island developing States (SIDS) have an even higher share of grants in their total commitments (67 per cent). ● This demonstrates that financial institutions are placing a higher emphasis on providing grant-based funding to LDCs and SIDS. This reflects concerns that traditional debt instruments (loans) are a less equitable option for adaptation finance in the most vulnerable countries, due to current debt vulnerabilities and limited fiscal capacity. ▶ Approximately a quarter of the finance simultaneously addressing both adaptation and mitigation (cross-cutting finance) was committed for general environment protection, indicating the potentially synergetic role of nature-based solutions for both adaptation and mitigation. ▶ Domestic expenditure and private finance are identified as vitally important sources of adaptation finance, but quantitative estimates continue to be unavailable. However, neither domestic expenditures nor private finance flows are likely to bridge the adaptation finance gap alone, especially in low-income countries (including the LDCs and SIDS), and there are important equity issues in using domestic budgets to address the finance gap in these countries.